A high temperature engine materials test facility - Shelton, Prabha H.; Wadley, Haydn N. G. (Review of scientific instruments, 2024)
Gas turbine engines subject materials to extreme conditions. Their high temperature materials and co-developed coatings must survive combustion gas temperatures currently approaching 1800 °C, large thermal gradients, severe thermal shock, and static and fatigue inducing applied stresses, all the while operating in highly reactive, high-pressure, high-speed combustion gas flows containing significant partial pressures of water vapor, oxygen, and other reactive species for many tens of thousands of hours. We describe the design and development of a test facility for the study of materials under individual and combinations of test parameters similar to those experienced within legacy and future engines. A hydraulic load frame capable of applying static or cyclic tension-compression stresses up to 400 MPa to flat-dog bone-shaped test specimens is integrated within an environmental test chamber capable of sustaining gas pressures from 0.1 to 1.2 MPa (1–12 atm). An adjustable 0.1–2 kW power CO2 laser whose 10.6 µm wavelength radiation is strongly absorbed by ceramic coating materials is used to heat sample surfaces to temperatures of 1800 °C and above, while rear surface air jet cooling establishes through-thickness thermal gradients. Rapid laser heating in conjunction with transiently applied front and/or rear-side air cooling is used to create hot or cold thermal shock effects. This is accompanied by the impingement of a high pressure (up to 1.3 MPa) reactive gas jet upon the sample with speeds up to 300 m/s by preheating dry air, mixing it with steam to the desired humidity, heating to 850 °C, and then expanding it through a converging nozzle. Thermal imaging pyrometers measure specimen front and back surface temperature fields, while environmental test chamber view ports permit digital image correlation and strain mapping.